2019
DOI: 10.1108/ecam-04-2019-0211
|View full text |Cite
|
Sign up to set email alerts
|

Physical and cognitive demands of work in building construction

Abstract: Purpose Investigating demands within an occupational context has always been an essential endeavor to guarantee worker well-being and performance efficiency. In blue-collar occupations, the physical demands of manual labor have always been the major focus, but recent technological changes may come with higher demands on the intellectual capacities of workers. For this reason, the purpose of this paper is to assess physical and cognitive demands that construction workers face. Design/methodology/approach The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Previous studies (Jebelli et al, 2019a;Choi et al, 2019;Aryal et al, 2017) also point out that physiological variables, which are ST, HR and EDA are crucial indicators to understand the mental and physical disorders of the construction workers. It is commonly emphasized that these human body reactions have vital roles in construction accidents (Rodriguez et al, 2019).…”
Section: Research Methodology 31 Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies (Jebelli et al, 2019a;Choi et al, 2019;Aryal et al, 2017) also point out that physiological variables, which are ST, HR and EDA are crucial indicators to understand the mental and physical disorders of the construction workers. It is commonly emphasized that these human body reactions have vital roles in construction accidents (Rodriguez et al, 2019).…”
Section: Research Methodology 31 Hypothesis Developmentmentioning
confidence: 99%
“…(Accepted) cognitive task as a mental stressor because recent research has found that construction workers suffer from higher cognitive workload as compared to workers in other industries (Azeez et al 2019). Also, the cognitive workload of construction workers is expected to increase further in the coming years due to the ongoing digitization of the construction industry (Rodriguez et al 2019). Last but not the least, other stressors such as working in hazardous environment and time-pressure may fail to induce mental stress under simulated environment when the participants know that it is just a simulation.…”
Section: Knowledge Gapmentioning
confidence: 99%
“…Construction work is both physically [1] and psychologically demanding [2]. Workers in the construction industry experience higher work disabilities than other blue-collar employees [3].…”
Section: Introductionmentioning
confidence: 99%